2020
DOI: 10.1038/s41598-020-67170-8
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of SIRT6 by DNA hypomethylating agents and clinical consequences on combination therapy in leukemia

Abstract: The FDA-approved DNA hypomethylating agents (DHAs) like 5-azacytidine (5AC) and decitabine (DAC) demonstrate efficacy in the treatment of hematologic malignancies. Despite previous reports that showed histone acetylation changes upon using these agents, the exact mechanism underpinning these changes is unknown. In this study, we investigated the relative potency of the nucleoside analogs and non-nucleoside analogs DHAs on DNA methylation reversal using DNA pyrosequencing. Additionally, we screened their effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…DNA repair pathways are DNA damage response mechanisms ( 28 , 29 ). DNA repair pathways influence cell survival and are anti-cancer therapeutic targets of radiotherapy and cytotoxic chemotherapy ( 30 , 31 ). γh2A is a major agent in DNA damage or repair ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA repair pathways are DNA damage response mechanisms ( 28 , 29 ). DNA repair pathways influence cell survival and are anti-cancer therapeutic targets of radiotherapy and cytotoxic chemotherapy ( 30 , 31 ). γh2A is a major agent in DNA damage or repair ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are a few indications wherein the SCAP promoter appears to be influenced by epigenetic modifications. Carraway et al (2020) have shown that histone H3K9 acetylation and DNA methylation can differentially regulate SCAP expression in leukemia cells although the involvement of specific histone/DNA modifying enzymes is not clear at this point. It would be of great interest to further examine the epigenetic mechanism whereby SCAP transcription is regulated to provide more flexibility in targeting the SREBP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation plays an important role in the regulation of the occurrence and development of AML ( 26 ). Some scholars have added DNA methylation inhibitors to refractory AML patients and found that the vast majority of AML patients can significantly prolong the survival time ( 24 ). Besides, the methylated GGH promoter associates with the variability of methotrexate responses in AML patients ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides DNA methylation being strongly associated with prognosis of AML patients, it has been reported that different methylation types have different clinical outcomes for AML patients ( 23 ). And DNA methylated genes can be used as therapeutic targets in AML ( 24 ).…”
Section: Introductionmentioning
confidence: 99%